Family theories - Klein, David M.; White, James M. (Los Angeles : Sage, 2008)
Contenido: What is a theory?. Philosophies of science. The functionalist framework. The social exchange and relational choice framework. The symbolic interaction framework. The family life course development framework. The conflict framework. The feminist framework and poststructuralist. The bioecological framework. The state of family theory and its future